Silane modified polyether sealant
By combining a coupling agent prepared using a specific method with silane-modified polyether resin and optimizing the component ratio, the adhesion problem of silane-modified polyether sealant in high-heat and high-humidity environments was solved, achieving high elastic recovery rate, low VOC release, high bonding strength, and high light transmittance.
Patent Information
- Application Number
- CN202511441837.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-10
- Publication Date
- 2025-12-05
AI Technical Summary
Existing silane-modified polyether sealants exhibit decreased adhesion under high heat and humidity conditions, resulting in poor sealing performance. Furthermore, it is difficult to achieve a balance between high elastic recovery rate, low VOC release, high bond strength, and light transmittance.
A coupling agent obtained by a specific preparation method is combined with a silane-modified polyether resin, and a smaller amount of coupling agent and crosslinking agent are used to optimize the component ratio and reaction conditions to prepare a silane-modified polyether sealant.
Without reducing elastic recovery rate and low VOC release, it improves bonding strength and light transmittance, and enhances adhesion in high heat and high humidity environments.
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of sealant synthesis, more particularly, to a silane modified polyether sealant. BACKGROUND
[0002] As a glass sealing outer layer glue, the silane modified polyether sealant has good compatibility with glass and metal, and has certain strength and elasticity, but the adhesion will decrease under alternating special environments such as high heat and high humidity, resulting in poor sealing and affecting the service life.
[0003] At present, many research teams have done a lot of research on silane modified polyether sealant, such as the applicant's previous improvement on the crosslinking agent used in the silane modified polyether sealant. Although the silane modified polyether sealant obtained can have low VOC, low tensile modulus and good storage stability, there are still certain limitations in industry, such as the obtained sealant cannot effectively balance high elastic recovery rate, low VOC, high adhesive strength and good light transmittance, and further improvement is needed. SUMMARY
[0004] The purpose of the present application is to provide a silane modified polyether sealant. In the present application, a coupling agent obtained by a specific preparation method is used in combination with a silane modified polyether resin to make the silane modified polyether sealant obtained by using a small amount of coupling agent can improve the adhesive strength and light transmittance while ensuring low VOC release without reducing the elastic recovery rate.
[0005] The silane modified polyether sealant provided by the present application is prepared from components including a silane modified polyether resin and a coupling agent. The mass ratio of the silane modified polyether resin and the coupling agent is 100: (1-3). The preparation method of the coupling agent comprises the following steps: under nitrogen protection, mixing ether, a first catalyst and epoxy silane, reacting at 55-65℃ for 2-3h, distilling at 100-110℃-0.06-0.04MPa after removing alcohol until no bubbles are generated, adding amino silane coupling agent, reacting at 70-80℃ until the system viscosity has no obvious increase, and cooling and filtering; the first catalyst is an organic tin Lewis acid, sodium alcoholate, potassium alcoholate, a solid super acid catalyst or a solid base catalyst.
[0006] The coupling agent obtained by the above specific preparation method is used in combination with a silane modified polyether resin and a crosslinking agent to prepare a silane modified polyether sealant, which only needs 1-3 parts of coupling agent (100 parts of silane modified polyether resin) to obtain a silane modified polyether sealant with better performance.
[0007] In a preferred embodiment of the present application, in the preparation method of the coupling agent, the ether is one or more of diethylene glycol monomethyl ether, diethylene glycol monobutyl ether, and triethylene glycol monomethyl ether, and preferably diethylene glycol monobutyl ether. The coupling agent prepared by using diethylene glycol monobutyl ether makes the elastic recovery rate of the foamed adhesive of the sealant higher. In a preferred embodiment of the present application, the molar ratio of the ether to the epoxy silane is (4-6):1. In the preparation method, if the amount of the ether is too small, the reaction is insufficient, the substitution rate of the ether chain for the alkoxy in the siloxy group is insufficient, and the use effect of the obtained coupling agent is affected. If the amount of the ether is too large, the recovery time is long, and the longer the high-temperature recovery time of the ether, the more prone to yellowing, which affects the color of the product.
[0008] In a preferred embodiment of the present application, in the preparation method of the coupling agent, the epoxy silane is γ-(2,3-epoxypropoxy)propyl trimethoxysilane, γ-(2,3-epoxypropoxy)propyl methyldiethoxysilane, γ-(2,3-epoxypropoxy)propyl triethoxysilane, 4-vinyl epoxy cyclohexyl trimethoxysilane, or 4-vinyl epoxy cyclohexyl triethoxysilane, and preferably γ-(2,3-epoxypropoxy)propyl trimethoxysilane.
[0009] In a preferred embodiment of the present application, in the preparation method of the coupling agent, the amino silane coupling agent is γ-aminopropyl triethoxysilane, γ-aminopropyl trimethoxysilane, N-β-aminoethyl-γ-aminopropyl trimethoxysilane, or γ-divinyl triaminopropyl trimethoxysilane, and preferably γ-aminopropyl trimethoxysilane. In a preferred embodiment of the present application, the molar ratio of the amino silane coupling agent to the epoxy silane is (1-2):1. If the amount of the amino silane coupling agent is too large, the crosslinking activity is high, the product is crosslinked fast, and the hardness is high. If the amount of the amino silane coupling agent is too small, the product is crosslinked slowly.
[0010] In a preferred embodiment of the present application, in the preparation method of the coupling agent, the first catalyst is HND-64 solid base catalyst. The use of the catalyst has high catalytic efficiency, does not affect the color of the product, and can make the effect of the obtained coupling agent best compared with other inorganic bases or sodium alcoholate catalysts. In the preparation method, the amount of the catalyst is preferably 2-5% of the mass of the epoxy silane. If the amount of the catalyst is too small, the reaction time is long, the reaction efficiency is low, and the effect of the obtained coupling agent is poor.
[0011] In the specific embodiment of the present application, in the preparation method of the coupling agent, the ether, the first catalyst and the epoxy silane are mixed under nitrogen protection, and reacted at 55-65°C for 2-3h. In the reaction, too high temperature can cause yellowing, and the coupling agent obtained by reacting for 2-3h has the best effect. In the preparation method, after the amino silane coupling agent is added, the reaction is carried out at 70-80°C until the viscosity of the system has no obvious increase (usually 3-5h of reaction can be achieved), and then the reaction is filtered after cooling to obtain the product. If the reaction temperature is too high after the amino silane coupling agent is added, yellowing can occur, and the reaction has the best effect at 70-80°C.
[0012] In the specific embodiment of the present application, the silane modified polyether sealant of the present application further comprises a crosslinking agent. When the coupling agent provided by the present application is used, only 3-8 parts of the crosslinking agent (100 parts of the silane modified polyether resin) is needed to achieve the effect of the present application. That is, the mass ratio of the silane modified polyether resin, the crosslinking agent and the coupling agent is 100:(3-8):(1-3).
[0013] In a preferred embodiment of the present application, the use of a specific crosslinking agent can further reduce the amount of the crosslinking agent and the coupling agent (to obtain a sealant with the same effect), and the preparation method of the crosslinking agent comprises the following steps: Under nitrogen protection, the vinyl trialkoxysilane and the orthosilicate are hydrolyzed in the presence of alcohol in a mixed solution of water and acid under catalysis, and then the product is obtained after impurity removal; the molar ratio of the vinyl trialkoxysilane, the orthosilicate and water is (0.8-1):(0.4-0.5):1. If the amount of the orthosilicate is too large, the crosslinking is too fast, which can cause the elastic modulus of the sealant to decrease, and if the amount of the vinyl trialkoxysilane is too small, the crosslinking effect is poor. In the preparation method of the crosslinking agent, the amount of the alcohol can be the conventional amount in the art, for example, it can be 20-50% of the mass of the vinyl trialkoxysilane, and the preparation method of the crosslinking agent in the present application is not specifically limited.
[0014] In a preferred embodiment of the present application, in the preparation method of the crosslinking agent, the vinyl trialkoxysilane is vinyl trimethoxysilane, vinyl triethoxysilane, vinyl tripropoxysilane or vinyl triisopropoxysilane; the orthosilicate is methyl orthosilicate, ethyl orthosilicate, propyl orthosilicate or isopropyl orthosilicate; and the alcohol is methanol, ethanol, n-propanol or isopropanol. More preferably, the alkyl group in the vinyl trialkoxysilane and the alkyl group in the orthosilicate are the same, and the alcohol is the alcohol corresponding to the silicon functional group in the vinyl trialkoxysilane. Further preferably, the vinyl trialkoxysilane is vinyl trimethoxysilane, the orthosilicate is methyl orthosilicate, and the alcohol is methanol. In this combination, the crosslinking activity of the obtained crosslinking agent is the highest.
[0015] In a preferred embodiment of the present application, in the preparation method of the crosslinking agent, the amount of acid is used to make the pH of the reaction system mixture 3-5, and the acid can be hydrochloric acid. In a specific embodiment, the preparation method of the crosslinking agent can specifically include the following steps: under nitrogen protection, mix vinyl trialkoxysilane and orthosilicate uniformly in 20-30% of methanol by mass of silane, drop 3-5h, and add a mixture of water and hydrochloric acid (the amount of hydrochloric acid is used to make the pH of the reaction system mixture 3-5) at 40-45℃, drop 3-5h, and heat for 1-2h, and then reflux for 3-4h, and then distill under normal pressure to 120-125℃, and then heat for 2-4h, and then cool down to obtain the crosslinking agent. The drop 3-5h can ensure the reaction efficiency and prevent excessive local hydrolysis from affecting the performance of the crosslinking agent. The condensation at 120-125℃ can reduce the residual silicon hydroxyl group and improve the viscosity and storage stability of the crosslinking agent. If the temperature is too high, it will bring out dimer and other oligomers, yellowing, and high energy consumption.
[0016] In a preferred embodiment of the present application, the components of the silane-modified polyether sealant further include a plasticizer, a filler, a thixotropic agent, an ultraviolet absorber, a light stabilizer, and a catalyst, i.e., the silane-modified polyether sealant is prepared from the following components: a silane-modified polyether resin, a crosslinking agent, a coupling agent, a plasticizer, a filler, a thixotropic agent, a light stabilizer, an ultraviolet absorber, and a catalyst, and the mass ratio of the specific components is 100: (3-8): (1-3): (80-100): (100-150): (1-10): (1-2): (1-2): (1-2).
[0017] In a preferred embodiment of the present application, the silane-modified polyether sealant is prepared from the following components: a silane-modified polyether resin, a crosslinking agent, a coupling agent, a plasticizer, a filler, a thixotropic agent, a light stabilizer, an ultraviolet absorber, and a catalyst.
[0018] In a specific embodiment of the present application, the silane-modified polyether resin is preferably an end silane-modified polyether resin with an average molecular weight of about 8000, the plasticizer is preferably PPG with an average molecular weight of 2000g / mol, the filler is preferably light calcium carbonate and heavy calcium carbonate, and the mass ratio of light calcium carbonate to heavy calcium carbonate is further preferably 2:1. The thixotropic agent can be one or more of polyamide wax, fumed white carbon black, and organic bentonite, and is preferably fumed white carbon black. The ultraviolet absorber is preferably RIASORB UV-3261 ultraviolet absorber. The light stabilizer is preferably a hindered amine light stabilizer, and is further preferably RIASORB UV-292 hindered amine light stabilizer. The catalyst is preferably stannous octoate.
[0019] In the detailed description of the present application, the preparation method of the silane-modified polyether sealant can be a conventional preparation method in the art, for example, comprising the following steps: mixing the silane-modified polyether resin, the plasticizer, the filler and the thixotropic agent in proportion, vacuum stirring and dehydrating at 110-120°C for 1h to prepare the base material; adding the crosslinking agent in the base material, and continuing to vacuum stir at high speed until the system is uniform; sequentially adding the ultraviolet absorber, the light stabilizer and the coupling agent, vacuum stirring at high speed until the system is uniform, and finally adding the catalyst, vacuum stirring at high speed and then discharging, to obtain the silane-modified polyether sealant.
[0020] The present application has the following beneficial effects: The coupling agent obtained by the specific preparation method is used in combination with the silane-modified polyether resin to improve the bonding strength (at least increased by more than 40%) and the light transmittance (for example, good glass transparency after immersion) of the obtained silane-modified polyether sealant under the premise of not reducing the elastic recovery rate (not less than 58%, preferably not less than 63%, and further preferably not less than 70%) and low VOC release (not more than 26g / kg, preferably not more than 21.5g / kg, and further preferably not more than 20g / kg), while improving the adhesion after ultraviolet irradiation. DETAILED DESCRIPTION
[0021] The detailed description of the specific embodiments of the present application is further described below in combination with examples. The following examples are used to illustrate the present application, but are not used to limit the scope of the present application. In the present application, unless otherwise specified, "%" is the mass percentage.
[0022] The preparation method of the silane-modified polyether sealant provided in the examples and comparative examples comprises the following steps: Mixing the silane-modified polyether resin, the plasticizer, the filler and the thixotropic agent, vacuum stirring and dehydrating at 90°C for 1h to prepare the base material; adding the crosslinking agent in the base material, and continuing to vacuum stir at high speed until the system is uniform; sequentially adding the ultraviolet absorber, the light stabilizer and the coupling agent, vacuum stirring at high speed until the system is uniform, and finally adding the catalyst, vacuum stirring at high speed and then obtaining the silane-modified polyether sealant.
[0023] Example 1 The components of the silane-modified polyether sealant provided in this example are as follows: 100 parts by weight of a silane-modified polyether resin with a molecular weight of about 8000, 90 parts by weight of a plasticizer PPG with a molecular weight of 2000g / mol, 120 parts of a mixture of light calcium carbonate and heavy calcium carbonate in a ratio of 2:1, and 10 parts of a thixotropic agent fumed white carbon black, 6 parts of a crosslinking agent, 1 part of an ultraviolet absorber RIASORB UV-234, 1 part of a light stabilizer RIASORB UV-770, 3 parts of a coupling agent and 1 part of stannous octoate.
[0024] The preparation method of the coupling agent is as follows: Under nitrogen protection, 421.8 g of diethylene glycol monobutyl ether, 118.2 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, and 3.8 g of HND-64 were mixed and heated to 60 °C. The mixture was kept at this temperature for about 2 hours. The alcohol was then collected by distillation at normal pressure. The mixture was then heated to 100-110 °C and cooled to -0.06 to -0.04 MPa until no more bubbles were generated. The temperature was then lowered to about 50 °C and 132.8 g of γ-aminopropyltrimethoxysilane was added. The mixture was heated to 70-72 °C and reacted for 3.5 hours. The viscosity of the sample was measured to be 47 mPa·s. After half an hour, there was no significant increase in viscosity. Heating was then stopped, and a pale yellow transparent liquid was obtained. The viscosity of this pale yellow transparent liquid was 53 mPa·s.
[0025] The preparation method of the crosslinking agent is as follows: Under nitrogen protection, 148.2 g of vinyltrimethoxysilane and 60.9 g of methyl orthosilicate were stirred evenly in 55 g of methanol. A mixture of water and hydrochloric acid (18 g of water and 0.1 mol / L hydrochloric acid, adjusted to pH 4.32) was added dropwise at 40-45 °C over 4 hours. After reacting at this temperature for 1 hour, the mixture was slowly heated to reflux for 3 hours. The mixture was then distilled at atmospheric pressure to 120-125 °C and reacted for 3.5 hours. The crosslinking agent was then obtained by cooling. The viscosity of this crosslinking agent was 4.2 mPa·s, and the content of vinyltrimethoxysilane was 0.82% and the content of methyl orthosilicate was 0.45%.
[0026] Example 2 The method provided in this embodiment is the same as that in Embodiment 1, except that: In the preparation method of the coupling agent, the amount of diethylene glycol monobutyl ether used is 3.8*0.5 mol, and the amount of γ-aminopropyltrimethoxysilane used is 1.6*0.5 mol. The resulting coupling agent is a pale yellow transparent liquid with a viscosity of 46 mPa·s.
[0027] In the preparation method of the crosslinking agent, 0.8 mol of vinyltrimethoxysilane and 0.5 mol of methyl orthosilicate are used.
[0028] Example 3 The method provided in this embodiment is the same as that in Embodiment 1, except that: In the preparation method of the coupling agent, the amount of diethylene glycol monobutyl ether used is 3.5 * 0.5 mol, and N-β-aminoethyl-γ-aminopropyltrimethoxysilane is used instead of γ-aminopropyltrimethoxysilane, with the amount of N-β-aminoethyl-γ-aminopropyltrimethoxysilane being 1.7 * 0.5 mol. The resulting coupling agent is a pale yellow transparent liquid with a viscosity of 42 mPa·s.
[0029] In the preparation method of the crosslinking agent, 0.8 mol of vinyltriethoxysilane and 0.5 mol of tetraethyl orthosilicate are used.
[0030] Example 4 The method provided in this embodiment is the same as that in Embodiment 1, except that: In the preparation method of the coupling agent, the amount of diethylene glycol monobutyl ether used is 3.8*0.5 mol, and the amount of γ-aminopropyltrimethoxysilane used is 1.3*0.5 mol. The resulting coupling agent is a pale yellow transparent liquid with a viscosity of 56 mPa·s.
[0031] In the preparation method of the crosslinking agent, 0.95 mol of vinyltrimethoxysilane and 0.45 mol of methyl orthosilicate were used. The obtained crosslinking agent contained 0.82% vinyltrimethoxysilane and 0.62% tetramethoxysilane.
[0032] Example 5 The method provided in this embodiment is the same as that in Embodiment 1, except that: In the preparation method of the coupling agent, triethylene glycol monomethyl ether replaces diethylene glycol monobutyl ether, with the amount of triethylene glycol monomethyl ether being 5.5 * 0.5 mol and the amount of γ-aminopropyltrimethoxysilane being 1.6 * 0.5 mol. The resulting coupling agent is a pale yellow transparent liquid with a viscosity of 64 mPa·s.
[0033] In the preparation method of the crosslinking agent, 0.84 mol of vinyltripropoxysilane and 0.48 mol of propyl orthosilicate were used. The obtained crosslinking agent contained 1.1% vinyltripropoxysilane and 0.78% propyl orthosilicate.
[0034] Example 6 The method provided in this embodiment is the same as that in Embodiment 1, except that: In the preparation method of the coupling agent, diethylene glycol monomethyl ether is used instead of diethylene glycol monobutyl ether, the amount of diethylene glycol monomethyl ether is 4.6*0.5 mol, and the amount of γ-aminopropyltrimethoxysilane is 1.2*0.5 mol. The resulting coupling agent is a pale yellow transparent liquid with a viscosity of 38 mPa·s.
[0035] In the preparation method of the crosslinking agent, 0.9 mol of vinyltrimethoxysilane and 0.4 mol of methyl orthosilicate were used. The obtained crosslinking agent contained 0.42% vinyltrimethoxysilane and 0.16% methyl orthosilicate.
[0036] Example 7 The method provided in this embodiment is the same as that in Embodiment 1, except that: The preparation method of the crosslinking agent is as follows: 148.2g of vinyltrimethoxysilane and 30g of methanol are mixed and heated to about 40℃. A mixture of water (14g) and hydrochloric acid is added dropwise, wherein the amount of hydrochloric acid is used to make the pH value of the system 4.5. Hydrolysis is carried out for 5 hours, alcohol is removed by distillation, and the mixture is kept at 120℃ for 2 hours. The mixture is then cooled to obtain the crosslinking agent.
[0037] Comparative Example 1 The method provided in this comparative example is the same as that in Example 1, except that: The coupling agent is γ-aminopropyltrimethoxysilane.
[0038] Comparative Example 2 The method provided in this comparative example is the same as that in Example 1, except that: The coupling agents are γ-aminopropyltrimethoxysilane and γ-(2,3-epoxypropoxy)propyltrimethoxysilane in a molar ratio of 1:1.
[0039] Experimental Example The silane-modified polyether sealants obtained in the examples and comparative examples were extruded and coated onto the joint between double-glazed glass and metal cladding at an extrusion temperature of 110°C. The appearance of the cured sealant, the transparency of the glass after immersion in water, and the adhesion after irradiation were visually inspected.
[0040] The silane-modified polyether sealants obtained in the examples and comparative examples were tested as follows: elastic recovery rate was tested according to GB / T13477.8-2017; immersion adhesion at a constant elongation was tested according to GB / T13477.11 to evaluate the adhesive performance of the sealant after long-term water immersion; adhesion after ultraviolet irradiation was tested according to ISO 4892-3 standard. VOCs were tested using GB / T 33372-2020 "Limits of Volatile Organic Compounds in Adhesives", and the results are shown in Table 1 below.
[0041] Table 1 ; Finally, the method of this invention is merely a preferred embodiment and is not intended to limit the scope of protection of this invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this invention should be included within the scope of protection of this invention.
Claims
1. A silane-modified polyether sealant, characterized by, The component is prepared from components including silane-modified polyether resin and coupling agent; The mass ratio of the silane-modified polyether resin and the coupling agent is 100:(1-3); The preparation method of the coupling agent comprises the following steps: under nitrogen protection, mixing ether, a first catalyst and epoxy silane, reacting at 55-65℃ for 2-3h, distilling at 100-110℃-0.06-0.04MPa after removing alcohol until no bubbles are generated, adding amino silane coupling agent, reacting at 70-80℃ until the viscosity of the system has no obvious increase, and cooling and filtering; the first catalyst is an organic tin Lewis acid, sodium alcoholate, potassium alcoholate, solid super acid catalyst or solid base catalyst.
2. The silane-modified polyether sealant of claim 1, wherein The ether is one or more of diethylene glycol monomethyl ether, diethylene glycol monobutyl ether, diethylene glycol monobutyl ether, triethylene glycol monomethyl ether and short-chain PPG, and is preferably diethylene glycol monobutyl ether.
3. The silane-modified polyether sealant of claim 1, wherein The epoxy silane is γ-(2,3-epoxypropoxy)propyl trimethoxysilane, γ-(2,3-epoxypropoxy)propyl methyldiethoxysilane, γ-(2,3-epoxypropoxy)propyl triethoxysilane, 4-vinyl epoxy cyclohexyl trimethoxysilane or 4-vinyl epoxy cyclohexyl triethoxysilane. The amino silane coupling agent is γ-aminopropyl triethoxysilane, γ-aminopropyl trimethoxysilane, N-β-aminoethyl-γ-aminopropyl trimethoxysilane or γ-divinyl triaminopropyl trimethoxysilane.
4. The silane-modified polyether sealant of claim 1, wherein The first catalyst is HND-64 solid base catalyst.
5. The silane-modified polyether sealant according to any one of claims 1 to 4, characterized in that, The molar ratio of the ether and the epoxy silane is (4-6):1, and the molar ratio of the amino silane and the epoxy silane is (1-2):
1.
6. The silane-modified polyether sealant according to any one of claims 1 to 4, characterized in that, The component further comprises a crosslinking agent, and the mass ratio of the silane-modified polyether resin, the crosslinking agent and the coupling agent is 100:(3-8):(1-3).
7. The silane-modified polyether sealant of claim 6, wherein The preparation method of the crosslinking agent comprises the following steps: Under nitrogen protection, hydrolysis reaction is carried out in the presence of alcohol under the catalysis of a mixture of water and acid, and the hydrolysis product is obtained after removing impurities; the molar ratio of the vinyl trialkoxysilane, the orthosilicate and water is (0.8-1):(0.4-0.5):
1.
8. The silane-modified polyether sealant of claim 7, wherein The vinyl trialkoxysilane is vinyl trimethoxysilane, vinyl triethoxysilane, vinyl tripropoxysilane or vinyl triisopropoxysilane; the orthosilicate is methyl orthosilicate, ethyl orthosilicate, propyl orthosilicate or isopropyl orthosilicate; and the alcohol is methanol, ethanol, n-propanol or isopropanol.
9. The silane-modified polyether sealant according to any one of claims 1 to 4, characterized in that, The component further comprises a plasticizer, a filler, a thixotropic agent, an ultraviolet absorber, a light stabilizer and a catalyst, and the mass ratio of the silane-modified polyether resin, the plasticizer, the filler, the thixotropic agent, the thixotropic agent, the light stabilizer, the ultraviolet absorber and the catalyst is 100:(80-100):(100-150):(1-10):(1-2):(1-2):(1-2).
10. The silane-modified polyether sealant of claim 9, wherein The component is prepared from components including silane-modified polyether resin, crosslinking agent, coupling agent, plasticizer, filler, thixotropic agent, ultraviolet absorber, light stabilizer and catalyst.